ChemInform Abstract: Electrophilic Fluorophosphonium Cations in Frustrated Lewis Pair Hydrogen Activation and Catalytic Hydrogenation of Olefins. Issue 1 (17th December 2015) - vom Stein, Thorsten; Perez, Manuel; Dobrovetsky, Roman; Winkelhaus, Daniel; Caputo, Christopher B.; Stephan, Douglas W.
Abstract: The hydrogenation of olefins is achieved using a combination of phoshorous(V)‐based Lewis acids with diaryl amines for the activation of dihydrogen.